ISOLASI, IDENTIFIKASI DAN UJI AKTIVITAS ANTIBAKTERI ISOLAT JAMUR ENDOFIT DAUN KENIKIR (Cosmos caudatus Kunth.) - Melzi Octaviani; Kolista Sisilawati; Elsa Safitri; Haiyul Fadhli; Emma Susanti; Armon Fernando (Jurnal Penelitian Farmasi Indonesia, 2026)
Kenikir (Cosmos caudatus Kunth.) is a plant used by the community as a traditional medicine and has antibacterial activity. Kenikir leaves contain secondary metabolite compounds such as alkaloids, flavonoids, phenolics and saponins. This plant has endophytic fungi that can produce the same bioactive compounds as its host. This study aims to isolate endophytic fungi from kenikir leaves, identify and test the antibacterial activity of endophytic fungi isolates from kenikir leaves against Gram-positive (Staphylococcus aureus and Bacillus cereus) and Gram-negative (Pseudomonas aeruginosa and Salmonella typhi) bacteria. Endophytic fungi were isolated from kenikir leaves, then purified to obtain a pure culture of endophytic fungi. Endophytic fungal isolates were then identified macroscopically and microscopically. Fermentation was carried out on endophytic fungal isolates to obtain supernatants, then tested for antibacterial activity using the disc diffusion method. The results of endophytic fungal isolation obtained 4 isolates, namely FECC-D1 (Alternaria sp.), FECC-D2 (Lichtheimia sp.), FECC-D3 (Canidiobolus sp.), FECC-D4 (Aspergillus sp.). The results of the antibacterial activity test of the supernatants of the four endophytic fungal isolates showed antibacterial activity. The results of data analysis using the One Way ANOVA test showed a significant difference in the diameter of the inhibition zone between the positive control and the supernatants of the endophytic fungal isolates. The supernatants of the 4 endophytic fungal isolates of kenikir leaves have activity in inhibiting the growth of pathogenic bacteria.